ANALISIS FAKTOR-FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI PENDAPATAN USAHATANI PADI SAWAH DI DESA SUKOREJO KECAMATAN SUKORJO KABUPATEN PONOROGO - Mochammad Zainul Arifin; Masyhuri Mahfudz; Sri Hindarti (Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2019)
ABSTRACTThis research aims to analyze social-economic factors that affect the rice farming income. The study was held in the village of sukorejo, denkorejo, the ponorogo district that was selected on purpose (purposive method). The method of sampling was used randomly by the number of respondents as many as 50 people. Data analytical methods used in this research are the Cobb-Douglas model with the unit output price technique or UOP Cobb Douglas Profit Funtion (UOP-CDPF) . The results of the analysis indicate that a large number of rice farmers in the village of sukorejo are profitable and efficient. Further, it is found that factors that have a real effect on income are the price of urea, the price of phonska fertilizer, and the wages of labor. Factors that have no effect on income are aducation, family members, the price of organic fertilizer, the cost of fertilizer, and medicine. Keywords: the rice fields; the efficiency; the ecnomic-social